Back Cover: Highly Ordered Mesoporous Few‐Layer Graphene Frameworks Enabled by Fe3O4 Nanocrystal Superlattices (Angew. Chem. Int. Ed. 19/2015). Issue 19 (2nd April 2015) - Jiao, Yucong; Han, Dandan; Liu, Limin; Ji, Li; Guo, Guannan; Hu, Jianhua; Yang, Dong; Dong, Angang
<x xml:space="preserve">Abstract</x> Highly graphitic frameworks with ordered mesoporosity and high surface areas are still challenging to prepare. In their Communication on page 5727 ff., A. Dong and co‐workers describe an elegant strategy that harnesses self‐assembled Fe3O4 nanocrystal superlattices to fabricate highly ordered mesoporous graphene frameworks with ultrathin pore walls consisting of three to six stacked graphene layers and a high surface area of approximately 1000 m2 g−1.